La Segunda Guerra Mundial en el Pacífico: estética cinematográfica y la ética de la guerra americana - Prorokova, Tatiana (Revista de Filología Románica, 2017)
U.S. involvement in both theatres of WWII, i.e., in Europe and in the Pacific, has been widely reflected in literature, film, music, and art. This paper investigates the way American intervention in the Pacific is showcased in Terrence Malick’s film The Thin Red Line (1998) and the miniseries The Pacific (2010), directed by, among others, Jeremy Podeswa, and produced by, among others, Tom Hanks. I seek to analyze the aesthetics and ethics of U.S. war in the Pacific that these two media project. Do the chosen examples justify American intervention? How was the war in the Pacific different from that one in Europe? Were U.S. soldiers ready to fight in the Pacific? How did the war influence its participants? These are some of the questions the paper will meditate upon in large detail.